Answers

2015-04-09T10:30:58+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
3 x^{2} -5x-2=0

3 x^{2} -6x+x-2=0

3x(x-2)+1(x-2)=0

(3x+1)(x-2)=0

x =  \frac{-1}{3} and x = 2
1 5 1
welcome ;)
approve my answ. shivam
yeah i had approve yrs ans
thnks
Yeah but i have noticed that we can't able to approve our answers.
2015-04-09T10:50:40+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
⇒ 3x² - 5x - 2
⇒ 3x² -6x + 1x - 2
⇒ 3x(x - 2) + 1(x - 2)
⇒ (3x + 1 ) ( x - 2 )
⇒ x =   \frac{-1}{3} , x = 2
1 5 1